Expected success factors in the procurement of public sector projects in Nigeria: a stakeholder analysis / Martin Dada - Dada, Martin Oloruntobi (Faculty of Architecture, Planning & Surveying & UiTM Press, 2013)
Perceptions, whether right or wrong, have the capacity for determining human interactions and responses to issues. Analysing and ultimately managing stakeholders' views have been recognized as necessary for the success of projects or programs. This research set out to investigate the expectations of client and consulting organizations in the Nigerian construction industry on priorities in public project procurement or implementation. An opinion survey of client and consulting organizations in some selected states of Nigeria was done. A set of 155 questionnaires was administered through the use of purposive and snow balling techniques on clients and consulting organizations. 65 completed questionnaires were returned. The data collected was subjected to both descriptive and inferential statistical analysis. The results of the analysis indicate that project completion at 'least or budgeted cosf is regarded as the most important issue of emphasis by consulting organizations while 'project meeting transparency and accountability' requirements is the most important to client organizations. The results further suggest that there are no significant differences, between client and consulting organizations in the rankings of the six identified expectations on public sector project implementation. It is recommended that the homogeneity of perceptions by the two organizations can form the basis of intervention efforts for improvements in public sector project delivery. Furthermore, the result provide the stakeholders of public projects feedback on perceptions, which can be useful in planning for future public projects.